Resveratrol reduces cardiac NLRP3‐inflammasome activation and systemic inflammation to lessen doxorubicin‐induced cardiotoxicity in juvenile mice. Issue 12 (6th May 2021) - Maayah, Zaid H.; Alam, Abrar S.; Takahara, Shingo; Soni, Shubham; Ferdaoussi, Mourad; Matsumura, Nobutoshi; Zordoky, Beshay N.; Eisenstat, David D.; Dyck, Jason R.B.
Abstract : Doxorubicin (DOX) is a very effective anticancer agent that is widely used in pediatric cancer patients. Nevertheless, DOX is known to have cardiotoxic effects that may progress to cardiomyopathy later in life. We have recently shown that cotreatment of resveratrol (RES) with DOX in juvenile mice attenuates late‐onset hypertension‐induced cardiomyopathy. However, the molecular mechanism responsible for these changes remains unknown. Herein, we show that the cardiac NLRP3 inflammasome plays a crucial role in regulating cardiac injury in a DOX ‐treated juvenile mouse model and the detrimental effects of hypertension in these mice later in life. We further demonstrate that RES significantly reduces systemic inflammation to contribute to the improvements observed in DOX ‐induced cardiac injury in young mice and late‐onset hypertension‐induced cardiomyopathy. Abstract :